On the identity of Collingwood’s Pill-Making Crab, Sphaerapoeia collingwoodii Collingwood, 1868 (Crustacea: Decapoda: Brachyura: Dotillidae) - Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2011)
The genusand species-group names Sphaerapoeia collingwoodii were made available in an account of the voyage of the H.M.S. Serpent by Collingwood (1868) for a species of intertidal ocypodoid crab found in Singapore, Labuan (Borneo) and Johore (Peninsular Malaysia). The names were used in Collingwood (1868) on the basis of a letter to him from Bate, who never published these names himself. Based on the morphological, ecological and locality notes given by Collingwood (1868), we identify Sphaerapoeia collingwoodii with the dotillid Scopimera intermedia Balss, 1934. We enact Article 23.9.2 of the Code to reverse precedence of these names, thereby making Scopimera intermedia Balss, 1934, a nomen protectum, and Sphaerapoeia collingwoodii Collingwood, 1868, a nomen oblitum.